Considerable decline in prostate cancer mortality in Nordic countries after 2000 - Rune Kvåle; Giske Ursin; Christian Ekanger; Bjørn Møller (Acta Oncologica)
Background and purpose: In the late 1990s, the Nordic countries, with Norway at the top, were among the countries with the highest prostate cancer mortality in the world. We present updated mortality rates from the Nordic countries and discuss possible interpretations of changes in trends.